2018
DOI: 10.2147/ppa.s175095
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to disease-modifying therapies in patients with multiple sclerosis

Abstract: BackgroundMultiple sclerosis (MS) is a chronic, inflammatory progressive demyelinating disease of the central nervous system. MS is one of the main causes of disability among young adults, and its management is a serious challenge for the healthcare system.PurposeThe main purpose of this study was to examine adherence to first-line disease-modifying therapy (DMT) in MS patients using the self-report Multiple Sclerosis Treatment Adherence Questionnaire (MS-TAQ).Materials and methodsThe participants consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…(Gilenya, which is taken orally once a day), natalizumab (Tysabri, which is injected intravenous once a once every four weeks), alemtuzumab (Lemtrada, which is injected intravenously just once a day for 5 days but which then repeats this routine each year thereafter), and mitoxantrone (Novantrone, which is injected intravenously) [4,5].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
See 1 more Smart Citation
“…(Gilenya, which is taken orally once a day), natalizumab (Tysabri, which is injected intravenous once a once every four weeks), alemtuzumab (Lemtrada, which is injected intravenously just once a day for 5 days but which then repeats this routine each year thereafter), and mitoxantrone (Novantrone, which is injected intravenously) [4,5].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Currently, the first-line drugs for MS include interferon beta-1a (Avonex, which is injected intramuscularly once a week, and Rebif, which is injected subcutaneously three times a week), interferon beta1b (Betaferon and Extavia, which are injected subcutaneously every other day), glatiramer acetate (Copaxone, which is injected subcutaneously every day or three times a week), dimethyl fumarate (Tecfidera, which is taken orally twice a day), and teriflunomide (Aubagio, which is taken orally once a day). The second-line drugs include fingolimod (Gilenya, which is taken orally once a day), natalizumab (Tysabri, which is injected intravenous once a once every four weeks), alemtuzumab (Lemtrada, which is injected intravenously just once a day for 5 days but which then repeats this routine each year thereafter), and mitoxantrone (Novantrone, which is injected intravenously) 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Until 2017, no study evaluating the degree of compliance with therapeutic recommendations in patients with multiple sclerosis treated with immunomodulation was conducted and published in Poland. Kołtuniuk and Rosińczuk [5] undertook such a task and conducted a study in four centres in Wrocław. The results of their research show that 76.5% of the studied patients comply with the therapeutic recommendations, which is also confirmed in the results of my work and the results of other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, only one study has been conducted and published so far, which examined the degree of compliance with therapeutic recommendations in patients with multiple sclerosis treated with first-line injectable immunomodulating drugs, without assessing oral drugs and second-line drugs [5]. Therefore, our own research was to answer the question of what is the level of compliance with therapeutic recommendations among patients from multiple sclerosis treated with drugs modifying the course of the first and second line disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have suggested that development of MS is influenced by genetic, environmental, and infectious agents [4] . To date, no curative treatment exists for patients with MS. Disease-modifying therapies are used nowadays only to reduce the progression of the disease and ameliorate the patient lifestyle [5] .…”
Section: Introductionmentioning
confidence: 99%